2015
DOI: 10.1016/j.annepidem.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between actigraphic sleep metrics and body composition

Abstract: Purpose Determine if individuals with poor sleep characteristics (i.e., late sleep onset or wake times, short sleep duration, long sleep latency, low sleep efficiency, high wake-after-sleep-onset [WASO]) have greater body mass index (BMI=kg/m2) or body fat. Methods Data for these cross-sectional analyses were from the Energy Balance Study (University of South Carolina). Participants were between 21 and 35 years of age and had a BMI of 20–35 kg/m2. Body fat percent was measured by dual X-ray absorptiometry. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
(83 reference statements)
2
17
2
3
Order By: Relevance
“…Additionally, we demonstrated that this population has lower sleep efficiency. Intriguingly, despite the fact that Hadza daily energy expenditure is comparable with western populations (Pontzer et al, ), we found an association between greater BMI and longer sleep duration, suggesting a difference between the Hadza and Western populations, where high BMI is associated with short sleep duration (Cappuccio et al, ; Wirth et al, ). One factor that might account for this difference concerns the actual values of BMI: in the Hadza, high BMI indicated someone who was in the “normal” range, whereas in Western populations, high BMI was associated with obesity.…”
Section: Discussioncontrasting
confidence: 54%
“…Additionally, we demonstrated that this population has lower sleep efficiency. Intriguingly, despite the fact that Hadza daily energy expenditure is comparable with western populations (Pontzer et al, ), we found an association between greater BMI and longer sleep duration, suggesting a difference between the Hadza and Western populations, where high BMI is associated with short sleep duration (Cappuccio et al, ; Wirth et al, ). One factor that might account for this difference concerns the actual values of BMI: in the Hadza, high BMI indicated someone who was in the “normal” range, whereas in Western populations, high BMI was associated with obesity.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, poor sleep quality was inversely associated with waist circumference in 400 Swedish females, aged 20-70 years (Theorell-Haglow et al, 2010). Further, a recent study found greater BMI and body fat percent were associated with low sleep quality among male and female Americans aged 21-35 years (Wirth et al, 2015). The possible explanation of the above finding is that insufficient sleep may increase energy needs, dietary consumption, the tendency to skip breakfast, eat less fruit/vegetables, and eat more each day and/or it may impact on hunger and satiety hormones (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…From a sleep health perspective, other studies have demonstrated that low sleep efficiency is associated with worse school achievement in adolescents, 41 higher body mass index and body fat, 42 negative daily mood in children, 43 and worse next-day anxiety and fatigue in persons with irritable bowel syndrome. 44 Therefore, an ambient lighting intervention designed to increase circadian entrainment and improve sleep can also impact populations beyond those studied in the present paper.…”
Section: Discussionmentioning
confidence: 99%